AfCHIL, a Type IV Chalcone Isomerase, Enhances the Biosynthesis of Naringenin in Metabolic Engineering - Xu, Huanhuan; Lan, Yanping; Xing, Jiayi; Li, Yi; Liu, Lecheng; Wang, Yongqin (Frontiers in Plant Science, 2022)
Naringenin is an essential precursor for all flavonoids, and effectively promoting naringenin production is crucial in metabolic engineering. The interaction between plant metabolic enzymes ensures metabolic flux. The effect can effectively improve the natural product synthesis of engineering microbial systems. In this study, chalcone isomerase genes in Allium fistulosum have been identified. The expression of AfCHIL is closely related to the accumulation of anthocyanins, and the expression of AfCHIL and AfCHS was highly synchronized. Yeast two-hybrid and firefly luciferase complementation imaging assay further confirmed AfCHIL physically interacted with AfCHS/AfCHI. The bioconversion experiment confirmed that AfCHIL reduced the derailment produced by AfCHS and increased the yield of naringenin. In addition, a system of biosynthesis naringenin involved in AfCHS was constructed, and these results suggested that the potential function between CHS with CHIL advanced naringenin production effectively. In conclusion, this study illustrated the function of AfCHIs in Allium fistulosum and provided new insight into improving the synthesis efficiency of naringenin.